2020
DOI: 10.1002/vzj2.20066
|View full text |Cite
|
Sign up to set email alerts
|

Pore water isotope fingerprints to understand the spatiotemporal groundwater recharge variability in ungauged watersheds

Abstract: Reliable groundwater recharge quantification at the regional scale (e.g., watershed or subwatershed) is fundamental to sustainable water resource management. Although modeling at the watershed scale is gaining wide support, the long-term monitoring needed for model calibration is often not readily available, as many watersheds worldwide remain ungauged. In response to this situation, we propose a new approach to estimate groundwater recharge at the watershed scale. This approach is fast and accurate and takes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
(71 reference statements)
0
13
0
Order By: Relevance
“…In all these examples DVE-LS analyses were performed on soil or rock samples. Although generally conceivable (Millar et al, 2018(Millar et al, , 2019, we are not aware of any published field study employing DVE-LS on plant samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all these examples DVE-LS analyses were performed on soil or rock samples. Although generally conceivable (Millar et al, 2018(Millar et al, , 2019, we are not aware of any published field study employing DVE-LS on plant samples.…”
Section: Introductionmentioning
confidence: 99%
“…They also tested different sample storage containers and favored Ziploc® freezer bags, which when doubled they found to reliably hold sample water and prevent significant evaporitic enrichment of heavy isotopes for up to 10 d. Comparing the DVE-LS method with analyses of liquid water squeezed from low-permeability samples, Nakata et al (2018) found the former to represent water from open pores only. Millar et al (2018) analyzed plant samples from a controlled environment in a direct comparison of the DVE-LS method against five quantitative water extraction methods. They found the former to be superior in terms of limited co-extraction of volatile organic compounds (VOCs), rapid sample throughput, and near-instantaneously returned stable isotope results.…”
Section: Introductionmentioning
confidence: 99%
“…The results from the hydro-isotopic water budget and from the model used in the present study were within the same order of magnitude and in good agreement. Mattei et al (2020a) estimated GR in the same region using water isotopic profiles. The estimated GR at SLZ for 2017 varied between 380 and 395 mm/y and from 158 to 214 in 2018.…”
Section: Long-term Groundwater Recharge Simulationmentioning
confidence: 99%
“…Under a wide variety of conditions, GR is still considered to be one of the most challenging water-balance components to quantify (Dripps and Bradbury 2007) because it is difficult to measure directly and it is strongly influenced by climate, soil heterogeneity and land use. A wide range of methods (Scanlon et al 2002) has been shown to be useful in assessing the quantity of water actually replenishing an aquifer, including isotopic profiles (Barbecot et al 2018;Mattei et al 2020a, b), remote sensing techniques (Jackson 2002), chloride mass balance (Szilagyi et al 2011), base flow separation (Hung Vu and Merkel 2019), unsaturated zone modeling (Hu et al 2019;Mattei et al 2020a), water balance models (Dubois et al 2021) and water table fluctuations (Crosbie et al 2005). The reliability of these methods depends on a variety of factors, including the availability of field data to describe site characteristics, such as soil type, vegetation and depth to the water table (Scanlon et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical and isotopic study of groundwater, usually termed "hydrogeochemistry" is an essential complement to physical studies to identify recharge and discharge zones, flow paths and water chemical evolution [1]. As it reflects inputs from recharge areas [2], as well as confinement conditions [3], hydrogeochemistry is also used in certain cases as a proxy for groundwater vulnerability [4]. Yet, hydrogeochemistry studies suffer the same limitations as those in physical hydrology: flow path reconstructions or chemical evolution of water are often based on limited spatial access to the aquifer, through the measurements, when available, in piezometers, water wells and natural sources.…”
Section: Introductionmentioning
confidence: 99%